Clinic, Diagnosis and Treatment of Chronic Tinnitus - Kitsera Al. (Львівський клінічний вісник)
Introduction. Noise in the ears (NE, tinnitus) means pathological hearing impairments or sound phenomena that occur in the ear or in the head and is one of the most common symptoms of a variety of pathological conditions. The problem of the tinnitus is not fully understood, as it can be associated with a large number of factors that affect not only the organ of hearing but also other systems and organs. NE, according to various data, have 15.0-40.0% of the population, 25.0% of those with an NE, it complained the life and professional activity, and even causes self-isolation. Therefore, in many countries there are magazines devoted to the issue of ear noises, societies of patients with NE are created, specialized clinics work. Aim. Determine the etiologic, pathogenetic and clinical aspects of patients with the main complaint about the HS and the rational principles of diagnosis and treatment of pathological conditions accompanied by HS.